2019
DOI: 10.28991/cej-2019-03091295
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Rooster Tail Jump and End Sill in Horseshoe Spillways

Abstract: In a horseshoe spillways, due to the collision of the falling nappes from their surround walls, in the center of spillway’s trough, a spatial hydraulic jump is formed that named “rooster tail”. This study by using the physical model of horseshoe spillway, investigates the form, height and length of rooster tail jump. Based on the analytical methods, the effective parameters on rooster tail jump’s height and height were determined and their interaction was investigated and linear relationships were proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, this wave was generated at greater distances. To put it in other terms, the amount of H=H av was elevated from 1.120 to 1.32, and that of l s was raised from 9.2 to 13.5 m. Hassanzadeh et al (2019) found that the height and length of w 1 had a linear relationship with the flow velocity. Therefore, with a boost in θ, the flow velocity rose, which brought about an increase in the height of w 1 .…”
Section: Impact Of Bottom Inclination Angle (θ)mentioning
confidence: 97%
“…Additionally, this wave was generated at greater distances. To put it in other terms, the amount of H=H av was elevated from 1.120 to 1.32, and that of l s was raised from 9.2 to 13.5 m. Hassanzadeh et al (2019) found that the height and length of w 1 had a linear relationship with the flow velocity. Therefore, with a boost in θ, the flow velocity rose, which brought about an increase in the height of w 1 .…”
Section: Impact Of Bottom Inclination Angle (θ)mentioning
confidence: 97%
“…In the aim to understand the behaviour of these transverse waves called also rooster tail waves [2][3][4] for supercritical flows in the bend chute, a plethora of studies were done by several authors.…”
Section: Introductionmentioning
confidence: 99%